A Contractile DNA Machine with Single-Stranded DNA as Fuel - Wang, Nengfei; Fu, Peiyu; Song, Jian; Li, Huafeng (Asian Journal of Chemistry, 2013)
In the present work, one circular DNA component is generated by the hybridization of short nucleic acids with the 3' and 5' ends of single-stranded DNA chains. A contractile DNA machine has been built by means of crosslinking of circular DNAs into nanowires. The machine is powered by DNA and can be operated between contracted and extended states. This device has potentials in many applications such as targeted medicine delivery, nonviral gene delivery and in-cell cargo transportation. Furthermore, in combination with the DNA nanotechnology folding strategy, such as DNA origami, the contractile DNA machine may transduce DNA hybridization energy into controlled contraction movement in the nano- and micrometer ranges, or even in the 3D DNA nanostructures with geometric complexities.